UX for XR : user experience design and strategies for immersive technologies - Hillmann, Cornel (Design thinking., 2021)
Extending traditional digital platforms to the new frontier of extended reality (XR) requires taking into account what best practices, new concepts, and conventions have been established and what learnings can be brought forward from case studies involving industry leaders. By looking at practical examples from the field of handheld AR breakthroughs, virtual reality (VR) success stories and experimental interaction concept of pioneering XR platforms, you'll see how it's possible to map out a framework of user experience (UX) guidelines to close in on opportunities and challenges that lay ahead. This book defines, identifies, and analyzes UX practices for XR environments and reviews the techniques and tools for prototyping and designing XR user interactions. You'll approach the design for experiential state and spatial cognition, using established UX key performance indicators, while taking into account the social dynamics, emotional framework and wider industry context. UX design and strategy for the XR space is a new frontier, so UX for XR focuses on case studies and industry research to illustrate the relationship between UX design and the growth of immersive technologies. Practical examples will demonstrate how you should apply UX design principles using designing interactions in XR by identifying the importance of spaces, senses and storyboarding. You will: Explore the challenges and opportunities of designing for XR See how spatial interaction is revolutionizing human computer interaction Examine sensory input and interaction beyond the screen Work with 3D Interaction Design and build a strong 3D UX Understand VR and AR essentials for emotion-rich user experiences Apply UX research techniques for the XR space.